Pengaruh Green Accounting, Profitabilitas Dan Aktivitas Operasional Perusahaan Terhadap Nilai Perusahaan: Studi Pada Perusahaan Manufaktur Tahun 2021-2023 - Komang Yuda Arigestwan; Astawa, I Gede Putu Banu (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effect of Green Accounting, Profitability, and Operational Activities of the Company on Firm Value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The research employs a quantitative approach using secondary data in the form of annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The sample in this study was determined using a purposive sampling method based on specific criteria, resulting in a total of 66 observational data. The data analysis technique used is multiple linear regression with the assistance of SPSS version 25 software. The results of the study show that: (1) partially, Green Accounting has a positive and significant effect on firm value, (2) partially, Profitability has a positive and significant effect on firm value, (3) partially, Operational Activities of the Company also have a positive and significant effect on firm value, and (4) simultaneously, the three independent variables have a significant effect on firm value.